RNF213 Mutations in an Ethnically Diverse Population with Moyamoya Disease - Cecchi, Alana C. (Stroke, 2014)
BACKGROUND AND PURPOSE: Moyamoya disease (MMD) is a rare, genetically heterogeneous cerebrovascular disease resulting from occlusion of the distal internal carotid arteries. A variant in the Ring Finger 213 gene (RNF213), altering arginine at position 4810 (p.R4810K), is associated with MMD in Asian populations. However, there is a lack of data on the role of RNF213 in MMD patients of additional ethnicities and diasporic Asian populations. We investigate the contribution of RNF213 alterations to MMD in an ethnically diverse population based in the United States (U.S). METHODS: We initially sequenced RNF213 exons 43, 44, 45 (encoding the eponymous RING finger domain), and exon 60 (encoding p.R4810K), in 86 ethnically diverse patients with MMD. Comprehensive exome sequencing data from 24 additional MMD patients was then analyzed to globally identify RNF213 variants. Segregation of variants with MMD and other vascular diseases was assessed in families. RESULTS: RNF213 p.R4810K was identified in 56% (9/16) of MMD patients of Asian descent, and not in 94 patients of non-Asian descent. 3.6% (4/110) of patients had variants in the exons encoding the RING finger domain. Seven additional variants were identified in 29% (7/24) of MMD patients who underwent exome sequencing. Segregation analysis supported an association with MMD for two variants, and a lack of association with disease for one variant. CONCLUSIONS: These results confirm that alterations in RNF213 predispose patients of diverse ethnicities to MMD, and that the p.R4810K variant predisposes individuals of Asian descent in the U.S. to MMD.